Defining deliberate practice and deliberate play in team sports - Smith, Anthony S; Enloe, Emily; Arnold, Karen (Journal of Health and Physical Literacy, 2025)
The purpose of this study is to develop a better understanding of the developmental practice and play activities of current NCAA Division I college athletes in team sports. The objectives of this study include: 1) Determine the role of deliberate practice and deliberate play in the development of college team sport athletes; 2) Determine which developmental activities align with the tenants of deliberate practice; and 3)Describe the values and beliefs of team sports athletes related to practice activities. The population for the study includes four sport teams at a small, private university in the South (N=61). The four teams to be invited to participate include women’s volleyball (n=15), women’s basketball (n=11), men’s basketball (n=15) and baseball (n=19). ANOVAs revealed several differences between teams in practice activities under team practice, solo practice, and training activities. Significant differences also exist in time spent in Team and Individual Offense, Controlled Scrimmage, and related activities such as showcase activities, watching game film, and evaluating others during game film. Correlations found a negative correlation between Team Offense and Individual Defense/Live Scrimmage. The student athletes in this study varied in their start times for sport overall and for their primary sport. Scores for fitness, strength and conditioning, speed and agility, and watching game film were lower on the importance ratings, even with the push for strength and conditioning across the sprots world and the increase of technology in athletics as a developmental tool. Findings from this study show that neither deliberate practice with specialization nor deliberate play with diversification can stand alone as the primary way to develop as a young athlete. Practice must take part in several areas, including private training, solo practice, team practice, and developmental/conditioning activities to be successful.